Analysis of the Implementation of Fixed Asset Accounting Based on Financial Accounting Standards Statement PSAK 216 at PT Perkebunan Nusantara (PTPN) IV - Ahmad, Alya Hamdini; Syarvina, Wahyu; Nasution, Yenni Samri Juliati (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2026)
This study aims to analyze the compliance of fixed asset accounting implementation at PTPN IV (Four) with the provisions of Statement of Financial Accounting Standards (PSAK) 216 concerning Fixed Assets. The research focuses on recognition, initial measurement, measurement after recognition, depreciation, retirement and disposal of fixed assets, and disclosure of fixed assets in the financial statements. The research method used is a qualitative method with a case study approach, utilizing the company's fixed asset data, financial statements, and other supporting documents. The results indicate that PTPN IV has generally implemented fixed asset accounting in accordance with PSAK 16. Based on these findings, this study recommends that the company strengthen internal policies related to periodic fixed asset evaluation, improve the quality and completeness of disclosures in financial statements, and develop an accounting information system capable of supporting the retirement and disposal process of assets more effectively. This research is expected to provide academic and practical contributions in improving the quality of fixed asset accounting implementation, particularly in state-owned plantation companies.